2019
DOI: 10.1097/01.ju.0000555213.74850.47
|View full text |Cite
|
Sign up to set email alerts
|

Mp12-20 the Impact of Alternative Alkalinizing Agents on 24-Hour Urine Collection Parameters

Abstract: perspective. Factors important to patients for surgical success after stone surgery have not been explored. We looked to determine patient factors important for surgical success, changes in such factors before and after surgery, and the quantity of criteria reduction for surgical success.METHODS: Established stone patients scheduled for renal stone surgery completed a modified patient centered outcome questionnaire (PCOQ) before and 6-8 weeks after surgery. The modified PCOQ evaluated multiple domains includin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…For example, contemporary literature has shown that oral intake of citric acid will not alter urinary citrate compared with potassium citrate and sodium bicarbonate, which can have a significant citraturic effect. 8–10 It is clear we must consider the accompanying cation for alkaline supplements.…”
mentioning
confidence: 99%
“…For example, contemporary literature has shown that oral intake of citric acid will not alter urinary citrate compared with potassium citrate and sodium bicarbonate, which can have a significant citraturic effect. 8–10 It is clear we must consider the accompanying cation for alkaline supplements.…”
mentioning
confidence: 99%